Zebrafish retinal defects induced by ethanol exposure are rescued by retinoic acid and folic acid supplement - Muralidharan, Pooja (Alcohol, 2014)
Fetal Alcohol Spectrum Disorder (FASD) is caused by prenatal alcohol exposure, producing craniofacial, sensory, motor, and cognitive defects. FASD is highly prevalent in low socioeconomic populations, which are frequently accompanied by malnutrition. FASD-associated ocular pathologies include microphthalmia, optic nerve hypoplasia, and cataracts. The present study characterizes specific retinal tissue defects, identifies ethanol-sensitive stages during retinal development, and dissects the effect of nutrient supplements, such as retinoic acid (RA) and folic acid (FA) on ethanol-induced retinal defects. Exposure to pathophysiological concentrations of ethanol (during midblastula transition through somitogenesis; 2–24 hours post fertilization [hpf]) altered critical transcription factor expression involved in retinal cell differentiation, and produced severe retinal ganglion cell, photoreceptor, and Müller glial differentiation defects. Ethanol exposure did not alter retinal cell differentiation induction, but increased retinal cell death and proliferation. RA and FA nutrient co-supplementation rescued retinal photoreceptor and ganglion cell differentiation defects. Ethanol exposure during retinal morphogenesis stages (16–24 hpf) produced retinal defects like those seen with ethanol exposure between 2–24 hpf. Significantly, during an ethanol-sensitive time window (16–24 hpf), RA co-supplementation moderately rescued these defects, whereas FA co-supplementation showed significant rescue of optic nerve and photoreceptor differentiation defects. Interestingly, RA, but not FA, supplementation after ethanol exposure could reverse ethanol-induced optic nerve and photoreceptor differentiation defects. Our results indicate that various ethanol-sensitive events underlie FASD-associated retinal defects. Nutrient supplements like retinoids and folate were effective in alleviating ethanol-induced retinal defects.